Boundary formation in Drosophila wing: Notch activity attenuated by the POU protein Nubbin. - Neumann, C.J.; Cohen, S.M. (Science, 1998)
Cell interactions mediated by Notch-family receptors have been implicated in the specification of tissue boundaries in vertebrate and insect development. Although Notch ligands are often widely expressed, tightly localized activation of Notch is critical for the formation of sharp boundaries. Evidence is presented here that the POU domain protein Nubbin contributes to the formation of a sharp dorsoventral boundary in the Drosophila wing. Nubbin represses Notch-dependent target genes and sets a threshold for Notch activity that defines the spatial domain of boundary-specific gene expression.